Regulation of energy expenditure during prolonged athletic competition - Foster, C.; Hoyos, J.; Earnest, C.; Lucia, A. (Medicine & Science in Sports & Exercise, 2005)
Background: Athletic competitions, such as the Tour de France, demand both momentary bursts of very high power output and the ability to provide high levels of energy expenditure for several weeks. As such, they provide a model of the ability for sustained muscular activity, which is important in terms of how humans are understood, not only as athletes, but also within an evolutionary context.